Ameliorating Impact of Prophylactic Intranasal Oxytocin on Signs of Fear in a Rat Model of Traumatic Stress - Renicker, Micah D.; Cysewski, Nicholas; Palmer, Samuel; Nakonechnyy, Dmytro; Keef, Andrew; Thomas, Morgan; Magori, Krisztian; Daberkow, David P. (Frontiers in Behavioral Neuroscience, 2018)
Oxytocin treatment reduces signs of long-term emotional stress after exposure to trauma; however, little is known about the potential protective effects of oxytocin treatment on behavioral and physiological changes associated with extreme stress exposure. The objective of this study was to investigate oxytocin treatment as a prophylactic measure against rat signs of fear. Two separate experiments were conducted in which the time of intranasal oxytocin administration differed. Intranasal oxytocin (1.0 µg/kg) was administered 5 min after daily exposure to foot shock in Experiment #1 and 1 h before foot shock in Experiment #2. In Experiment #1, possible massage-evoked oxytocin release (5 min after foot shock) was also investigated. In both experiments, a contextual fear conditioning procedure was employed in which stress was induced via inescapable foot shock (3 days, 40 shocks/day, 8 mA/shock) in a fear conditioning chamber. Male Sprague-Dawley rats (n=24) were divided into four groups (n=6, per group) for each experiment. Experiment #1 groups: Control Exp#1 (intranasal saline and no foot shock); Stress Exp#1 (intranasal saline 5 min after foot shock); Massage+Stress Exp#1 (massage-like stroking and intranasal saline 5 min after foot shock); Oxytocin+Stress Exp#1 (intranasal oxytocin 5 min after foot shock). Experiment #2 groups: Control Exp#2 (intranasal saline and no foot shock); Stress Exp#2 (intranasal saline 1 h before foot shock); Oxytocin Exp#2 (intranasal oxytocin and no foot shock); Oxytocin+Stress Exp#2 (intranasal oxytocin 1h before foot shock). One week after fear conditioning (and other treatments), rats were independently evaluated for behavioral signs of fear. Two weeks after conditioning, physiological signs of fear were also assessed (Experiment #1). Relative to controls, rats treated with intranasal oxytocin 5 min after daily foot shock sessions exhibited significantly less immobility upon re-exposure to the shock chamber and attenuated physiological responses related to fear (e.g. elevated heart rate and blood pressure). Furthermore, intranasal oxytocin treatment given 1 h before daily foot shock sessions significantly decreased immobility and defecation upon re-exposure to the shock chamber, relative to controls. The results of this study suggest that prophylactic intranasal oxytocin, administered contemporaneously with aversive stimuli, mitigates behavioral and physiological responses associated with traumatic stress.